The Role of Transjugular Intrahepatic Portosystemic Shunt (TIPS) in Treating Portal Hypertension in Patients with Hepatocellular Carcinoma - Daniele Balducci; Michele Montori; Federico De Blasio; Alessandro Di Bucchianico; Maria Eva Argenziano; Gianluca Svegliati Baroni; Emidio Scarpellini (Medicina, 2023)
Liver cancer is very frequent, and hepatocellular carcinoma (HCC) accounts for the majority of liver cancer cases. Its growing incidence has been greatly affected by the increasing prevalence of metabolic-associated fatty liver disease (MAFLD). The latter is a new epidemic in our era. In fact, HCC is often generated from noncirrhotic liver and its treatment benefits from surgical and nonsurgical approaches, potentially bridged by transjugular intrahepatic portosystemic shunt (TIPS) use. TIPS use is an effective treatment for portal hypertension complications, but its application in patients with HCC and clinically significant portal hypertension (CSPH) remains controversial due to concerns about tumor rupture, dissemination, and increased toxicity. The technical feasibility and safety of TIPS use in HCC patients have been evaluated in several studies. Despite concerns about intraprocedural complications, retrospective studies have shown high success rates and low complication rates in TIPS placement for HCC patients. TIPS use in combination with locoregional treatments, such as transarterial chemoembolization (TACE) or transarterial radioembolization (TARE), has been explored as a treatment option for HCC patients with portal hypertension. These studies have shown improved survival rates in patients undergoing TIPS in combination with locoregional treatments. However, the efficacy and toxicity of TACE in combination with TIPS use require careful evaluation, as changes in venous and arterial flow can affect treatment outcomes and complications. The results from studies evaluating the impact of TIPS on systemic therapy and surgical options are also promising. In conclusion, the TIPS is a sufficiently safe, useful item available for physicians treating complications of portal hypertension. Moreover, a TIPS can be used in combination with locoregional therapy in HCC patients. Systemic chemotherapy can also benefit of the use of TIPS placement. A complex interplay affects TIPS use with surgery. The latter needs further data. The TIPS is a useful and safe add-on treatment, changing the natural course of HCC progression. Its use is regulated by a sophisticated physiologic and pathophysiologic flow of evidence.